Ubiquitination of Nonhistone Proteins in Cancer Development and Treatment - Zhang, Xiuzhen; Meng, Tong; Cui, Shuaishuai; Feng, Ling; Liu, Dongwu; Pang, Qiuxiang; Wang, Ping (Frontiers in Oncology, 2021)
Ubiquitylation, a crucial post-translation modification regulates the localization and stability of the substrate proteins including nonhistone proteins. The ubiquitin-proteasome system (UPS) on nonhistone proteins plays a critical role in many cellular processes such as DNA repair, transcription, signal transduction and apoptosis. Its dysregulation induces various diseases including cancer, and the identification of this process may provide potential therapeutic targets for cancer treatment. In this review, we summarize the regulatory roles of key UPS members on major nonhistone substrates in cancer-related processes, such as cell cycle, cell proliferation, apoptosis, DNA damage repair, inflammation and T cell dysfunction in cancer. In addition, we also highlight novel therapeutic interventions targeting the UPS members (E1s, E2s, E3s, proteasomes and deubiquitinating enzymes). Furthermore, we discuss the application of proteolysis-targeting chimeras (PROTACs) technology as a novel anticancer therapeutic strategy in modulating protein target levels with the aid of UPS.